Revisiting Church Down: experimental reconstructions at Butser Ancient Farm - Creighton, Trevor (Medieval Settlement Research, 2024)
The Mid Saxon settlement at Church Down, Hampshire, is one of the most significant sites of its type; the excavations have never, however, been the subject of a complete published report. Two experimental houses have been constructed at Butser Ancient Farm, Hampshire, each based upon specific archaeology from Church Down. As part of the process, available literature on Church Down was reviewed, which revealed the limited extent of the published material. This paper provides a fresh evaluation of the Church Down settlement through a synthesis of the published papers, updated with material from more recent evaluations of the archaeology and landscape in the environs. It includes an overview of the excavation and site character, an examination of the archaeology on which the Butser buildings are based, and details the interpretation of the archaeology as experimental structures.